Method for suppressing the adhesion of harmful substances to the air

By using metal oxides of specific particle sizes and non-decomposed particles in external agents, nanoscale surface unevenness is formed, which solves the problem of adhesion of harmful substances in air and maintains the smoothness of the skin after use.

JP7671571B2Active Publication Date: 2025-05-02KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020098002
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-06
Filing Date
2020-06-04
Publication Date
2025-05-02
Estimated Expiration
2040-06-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent the adhesion of harmful substances from air to the skin. At the same time, when using external agents, the metal oxide powder in the light protectant causes poor skin feeling.

Method used

An external agent containing metal oxides with specific particle sizes and non-decomposed particles is used to reduce the contact area of ​​air harmful substances with the skin by forming nanoscale surface unevenness, thereby inhibiting their adhesion.

Benefits of technology

It effectively inhibits adhesion to harmful substances in the air and maintains the smoothness of the skin after application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671571000006
    Figure 0007671571000006
  • Figure 0007671571000001
    Figure 0007671571000001
  • Figure 0007671571000002
    Figure 0007671571000002
Patent Text Reader

Abstract

To provide an air hazardous substance adhesion inhibiting method that enables a high adhesion inhibiting effect on air hazardous substances and achieves excellence in the feel after its application to the skin, particularly in the feeling of dryness and smoothness.SOLUTION: Provided is a an air hazardous substance adhesion inhibiting method which applies an external preparation to the skin to thereby inhibit air hazardous substances from adhering to the skin, the external preparation containing the following component (A) and component (B), and the mass ratio between the content of the component (A) and the content of the component (B) being 0.30 or more and 5.0 or less. Component (A): a metal oxide having an average primary particle diameter dA of 800 nm or less. Component (B): non-disintegratable particles having an average primary particle diameter DB of 1 μm or more and 10 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for suppressing adhesion of atmospheric hazardous substances. [Background technology]

[0002] In recent years, harmful substances suspended in the air, such as pollen from cedars and cypresses, soot, dust, and other air pollutants, and yellow sand (hereinafter also referred to as "air hazardous substances"), have become a problem because they cause various health damages to the human body. Among the air hazardous substances, particulate matter with a diameter of 2.5 μm or less, called PM2.5, is composed of carbon components, sulfates, nitrates, ammonium salts, and the like, and it is known that PM2.5 and yellow sand cause diseases of the circulatory system and respiratory system when inhaled. It has also been pointed out that PM2.5, pollen, and yellow sand cause skin troubles by adhering to or penetrating the skin. For example, Non-Patent Document 1 contains an academic report on the damage caused by PM2.5 to the skin. Therefore, there is a strong demand for cosmetics that protect the skin from air hazardous substances. For example, Patent Document 1 describes a skin care cosmetic that contains a specific amount of magnesium aluminometasilicate and a specific amount of an ultraviolet protection agent as a skin care cosmetic that protects the skin from external stimuli such as air pollutants. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2014 / 136993 [Non-patent literature]

[0004] [Non-Patent Document 1] Shiraiwa et al., Nature Chemistry 3, 291-295 (2011) Summary of the Invention [Problem to be solved by the invention]

[0005] In the technology of Patent Document 1, it is described that magnesium aluminometasilicate adsorbs air pollutants by its adsorption ability and does not reach the skin, and even if an acidic substance adheres, it can be neutralized by its pH buffering ability, thereby reducing skin damage caused by these external stimuli. It is also described that UV protection agents effectively protect the skin from UV rays. Although such technology can reduce the effects of air pollutants on the skin, it does not prevent the adhesion of air pollutants to the skin, and there is room for improvement. In addition, when inorganic powders such as titanium oxide and zinc oxide are blended as UV protection agents in an external preparation, the feel after application of the external preparation to the skin, especially the smooth feeling, may be poor. Therefore, a good feel after application is also required. An object of the present invention is to provide a method for inhibiting adhesion of atmospheric hazardous substances, which has a high effect of inhibiting adhesion of atmospheric hazardous substances and also provides an excellent feeling, particularly a smooth feeling, after application to the skin. [Means for solving the problem]

[0006] The present inventors have found that the above-mentioned problem can be solved by applying to the skin an external preparation containing a specified mass ratio of a metal oxide having an average primary particle size within a specified range and non-disintegrating particles having an average particle size within a specified range, rather than adsorbing air pollutants as in Patent Document 1, and forming nano-sized irregularities on the skin surface, thereby suppressing adhesion of air hazardous substances to the skin without impairing the feel of the skin after application. That is, the present invention provides the following [1] and [2]. [1] A method for suppressing adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, comprising: The topical preparation contains the following components (A) and (B), and the mass ratio of the content of component (A) to the content of component (B) in the topical preparation [(A) / (B)] is 0.30 or more and 5.0 or less. Component (A): Average primary particle diameter d A Metal oxide with a diameter of 800 nm or less Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less [2] The following components (A) and (B): Component (A): Average primary particle diameter d A Metal oxide with a diameter of 800 nm or less Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less Contains The component (B) is a composite particle (B1) in which at least a part of the surface of a core particle (b1-1) is coated with inorganic fine particles (b1-2), the core particles (b1-1) are one or more particles selected from poly(meth)acrylate particles and silica particles; the surface of the core particle (b1-1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines; the inorganic fine particles (b1-2) are one or more selected from titanium oxide and zinc oxide that have been surface-treated with one or more selected from silica, hydrous silica, and aluminum hydroxide; A topical preparation, in which the mass ratio of the content of component (A) to the content of component (B) [(A) / (B)] is 0.30 or more and 5.0 or less. Effect of the Invention

[0007] According to the present invention, it is possible to provide a method for inhibiting the adhesion of atmospheric hazardous substances, which has a high effect of inhibiting the adhesion of atmospheric hazardous substances and also provides an excellent feeling, particularly a smooth feeling, after application to the skin. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram showing a method for evaluating the effect of suppressing adhesion of atmospheric hazardous substances. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Methods for preventing the adhesion of harmful substances to the atmosphere] The method for inhibiting the adhesion of atmospheric hazardous substances of the present invention is a method for inhibiting the adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, wherein the external preparation contains the following components (A) and (B), and the mass ratio [(A) / (B)] of the content of component (A) to the content of component (B) in the external preparation is 0.30 or more and 5.0 or less. Component (A): Average primary particle diameter d A Metal oxide with a diameter of 800 nm or less Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less In the present invention, "harmful air substances" refers to air pollutants such as pollen from cedar, cypress, etc.; soot and smoke such as sulfur oxides, soot dust, nitrogen oxides, particulate matter, automobile exhaust gas, harmful air pollutants such as benzene, trichloroethylene, tetrachloroethylene, and particles containing volatile organic compounds (VOCs); and harmful substances suspended in the air such as yellow sand (including PM2.5).

[0010] The adhesion inhibiting method of the present invention is highly effective in inhibiting the adhesion of air hazardous substances, particularly air hazardous substances in the form of fine particles, and also provides an excellent feel (smooth feeling) after application to the skin. The reason for this is unclear, but is thought to be as follows. In the present invention, by applying a metal oxide having an average primary particle size within a predetermined range to the skin, nano-sized irregularities are formed on the skin surface, which reduces the contact area when atmospheric hazardous substances come into contact with the metal oxide, and is thought to effectively suppress the adhesion of atmospheric hazardous substances. The topical agent used in the present invention contains the metal oxide and non-disintegrating particles having a specific average particle size in a specific mass ratio. The non-disintegrating particles applied to the skin surface are unlikely to disintegrate even when rubbed and can maintain a specific particle size, which is thought to result in a good feel (smooth feel). In the following description, the effect of inhibiting adhesion of atmospheric harmful substances in the present invention will be referred to simply as "adhesion inhibiting effect", and the feel (smooth feel) in the present invention will be referred to simply as "feel".

[0011] <External preparations> [Component (A)] Component (A) has an average primary particle diameter d A It is a metal oxide having a diameter of 800 nm or less. Average primary particle diameter d of component (A) A From the viewpoint of improving the adhesion suppression effect, the average primary particle diameter d is 800 nm or less, preferably 500 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, still more preferably 80 nm or less, and even more preferably 50 nm or less, and from the viewpoint of versatility, it is preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. A From the viewpoint of improving the adhesion suppression effect and from the viewpoint of versatility, the thickness is preferably 1 to 800 nm, more preferably 1 to 500 nm, even more preferably 1 to 300 nm, still more preferably 1 to 200 nm, still more preferably 1 to 80 nm, still more preferably 5 to 80 nm, still more preferably 5 to 50 nm, and still more preferably 10 to 50 nm. The average primary particle diameter d A can be obtained from an image observed by a transmission electron microscope (TEM). Specifically, the maximum short diameter of 300 primary particles in the observed image is measured under conditions of a magnification of 50,000 times by a TEM, and the number average value is calculated. Here, the maximum short diameter means the short diameter having the maximum length among the short diameters perpendicular to the long diameter when the component (A) has a shape other than a plate shape. When the component (A) has a plate shape, the thickness of 300 primary particles in the observed image observed under the same conditions as above is measured, and the number average value is calculated. Specifically, it is measured by the method described in the examples.

[0012] Component (A) is not particularly limited as long as it is one that is commonly used in external preparations such as cosmetics. Specific examples include titanium oxide, zinc oxide, cerium oxide, aluminum oxide (alumina), magnesium oxide, calcium oxide, zirconium oxide, iron oxide, and chromium oxide. Among these, from the viewpoint of imparting ultraviolet protection ability, preferably one or more selected from titanium oxide, zinc oxide, and cerium oxide, more preferably one or more selected from titanium oxide and zinc oxide, and from the viewpoint of further improving the adhesion suppression effect, more preferably titanium oxide. When component (A) is titanium oxide, the crystal structure of the titanium oxide may be any of anatase, rutile, and brookite types, but from the viewpoint of versatility, the rutile or anatase type is preferred.

[0013] The shape of component (A) may be spherical, spindle-like, plate-like, needle-like, etc. Among these, from the viewpoint of improving the adhesion suppression effect, spherical, spindle-like, and plate-like shapes are preferred. When component (A) is titanium oxide, it is preferably spindle-shaped from the viewpoint of improving the adhesion suppression effect. When component (A) is zinc oxide, it is preferably spherical or plate-like in order to improve the adhesion suppression effect. The form of the component (A) is the average primary particle diameter d A As long as the above-mentioned range is satisfied, the toner may be in the form of primary particles, or may be in the form containing aggregates (secondary particles) formed by aggregation of primary particles.

[0014] Component (A) may be surface-untreated or surface-treated, but from the viewpoint of increasing the dispersibility of component (A) in the topical preparation and improving the adhesion suppression effect, it is preferable to treat the surface to modify it. Examples of surface treatment include hydrophobic treatment and hydrophilic treatment, and from the same viewpoint as above, hydrophobic treatment is preferable.

[0015] Examples of hydrophobic treatments include silicone treatment, alkylalkoxysilane treatment, fatty acid treatment, treatment with fluorine-containing compounds such as perfluoroalkyl phosphate esters, perfluoroalcohols, and perfluoroalkylalkoxysilanes, treatment with amino acids such as N-acylglutamic acid, and alkyl phosphate ester treatment. These surface treatments may be used alone or in combination of two or more. Among these, from the viewpoint of increasing the dispersibility of component (A) in the topical preparation and improving the adhesion suppression effect, one or more treatments selected from silicone treatment, alkylalkoxysilane treatment, and fatty acid treatment are preferred.

[0016] Examples of the surface treatment agent used in silicone treatment include various silicone oils such as methyl polysiloxane, dimethyl polysiloxane, methyl phenyl polysiloxane, methyl hydrogen polysiloxane, methyl cyclo polysiloxane, dodecamethyl cyclohexasiloxane, tetradecamethyl hexasiloxane, dimethyl siloxane / methyl (polyoxyethylene) siloxane / methyl (polyoxypropylene) siloxane copolymer, dimethyl siloxane / methyl (polyoxyethylene) siloxane copolymer, dimethyl siloxane / methyl (polyoxypropylene) siloxane copolymer, dimethyl siloxane / methyl cetyl oxy siloxane copolymer, dimethyl siloxane / methyl stearoxy siloxane copolymer, (alkyl acrylate / dimethicone) copolymer, etc. Among these, methyl hydrogen polysiloxane and dimethyl polysiloxane are preferred from the viewpoint of increasing the dispersibility of component (A) in the topical agent and improving the adhesion suppression effect.

[0017] As the surface treatment agent used in the alkylalkoxysilane treatment, from the viewpoint of increasing the dispersibility of component (A) in the topical agent and improving the adhesion suppression effect, those having a linear or branched alkyl group having from 6 to 20 carbon atoms are preferred, and octyltriethoxysilane and octyltrimethoxysilane are more preferred. Examples of the surface treatment agent used in the fatty acid treatment include linear or branched fatty acids having from 12 to 22 carbon atoms. Among them, from the viewpoint of increasing the dispersibility of component (A) in the topical preparation and improving the adhesion suppression effect, linear or branched higher fatty acids having from 14 to 22 carbon atoms are preferred, linear or branched higher fatty acids having from 16 to 20 carbon atoms are more preferred, and stearic acid and isostearic acid are even more preferred.

[0018] The above-mentioned surface treatment agents may be used alone or in combination of two or more. The amount of the hydrophobization treatment in component (A) is preferably 0.1% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, relative to component (A), from the viewpoint of increasing the dispersibility of component (A) in the topical preparation and improving the adhesion suppression effect. In addition, when the component (A) has been subjected to a hydrophobic treatment on its surface, the mass, coating amount and average primary particle diameter d A is the mass including the surface treatment agent, the coating amount, and the average primary particle diameter d A means...

[0019] When component (A) is titanium oxide, the content of TiO2 in the titanium oxide is preferably 60 mass% or more, more preferably 70 mass% or more, and preferably 100 mass% or less, from the viewpoint of improving the adhesion suppression effect. When component (A) is zinc oxide, the ZnO content in the zinc oxide is preferably 60 mass % or more, more preferably 70 mass % or more, and preferably 100 mass % or less, from the viewpoint of improving the adhesion suppression effect.

[0020] From the viewpoint of increasing the dispersibility of component (A) in the topical preparation and improving the adhesion-inhibiting effect, component (A) is preferably one or more selected from hydrophobically treated titanium oxide and hydrophobically treated zinc oxide, more preferably one or more selected from silicone-treated titanium oxide, silicone-treated zinc oxide, alkylalkoxysilane-treated titanium oxide, alkylalkoxysilane-treated zinc oxide, fatty acid-treated titanium oxide, and fatty acid-treated zinc oxide, and even more preferably one or more selected from fatty acid-treated titanium oxide and alkylalkoxysilane-treated zinc oxide.

[0021] Commercially available products of component (A) include "JR-800S" (silicone-treated titanium oxide), "MPY-70M" (silicone-treated titanium oxide), "MZ-504R3M" (silicone-treated zinc oxide), "MT-600KS" (silicone-treated zinc oxide), "MT-100TV" (stearic acid-treated titanium oxide), and "MT-100Z" (stearic acid-treated titanium oxide) manufactured by Teika Co., Ltd.; "MPT-171" (stearic acid-treated titanium oxide) manufactured by Ishihara Sangyo Kaisha, Ltd.; and "D-FZN" (silicone-treated titanium oxide) manufactured by Daito Kasei Kogyo Co., Ltd. Silicone-treated zinc oxide); Sakai Chemical Industry Co., Ltd.'s "STR-100A-LP" (silicone-treated titanium oxide), "FINEX-50-LPTM" (silicone-treated zinc oxide), "FINEX-30-OTS" (octyltriethoxysilane-treated zinc oxide), "STR-100C-LF" (stearic acid-treated titanium oxide), "STR-100W-OTS" (octyltriethoxysilane-treated titanium oxide), "FINEX-50-OTS" (octyltriethoxysilane-treated zinc oxide), etc.

[0022] [Component (B)] Component (B) has an average particle size of D B The particle size is 1 μm or more and 10 μm or less. In the present invention, "non-disintegrating particles" refer to particles that are difficult to disintegrate when rubbed under a prescribed load. Specifically, in the test method for confirming disintegrability described in the Examples, when rubbed back and forth 10 times using a surface property tester Tribogear Type: 14 (manufactured by Shinto Scientific Co., Ltd.), the particle size ratio before and after rubbing, represented by the following formula (I), is 50% or more. Particle size ratio before and after scraping (%) = (average particle size after scraping D B ' / Average particle size before abrasion D B )×100 (I) Average particle diameter D B From the viewpoint of providing a good feel after application to the skin, the average particle diameter D is 1 μm or more, preferably 2 μm or more, more preferably 3 μm or more, and from the viewpoint of improving the adhesion suppression effect, the average particle diameter D is 10 μm or less, preferably 9 μm or less, more preferably 8 μm or less. B The specific range of the average particle diameter D is preferably 1 to 9 μm, more preferably 2 to 9 μm, even more preferably 3 to 9 μm, and even more preferably 3 to 8 μm, from the viewpoint of improving the adhesion suppression effect and from the viewpoint of improving the feel after application to the skin. B is measured by the method described in the Examples.

[0023] The component (B) is preferably at least one type selected from inorganic particles and organic particles. Examples of inorganic particles include silicon dioxide (silica), silicon nitride, silicon carbide, aluminum silicate, magnesium silicate, calcium silicate, and other silicon-containing compounds; titanium oxide, zinc oxide, aluminum oxide (alumina), magnesium oxide, calcium oxide, zirconium oxide, iron oxide, cerium oxide, and chromium oxide, and other metal oxides; magnesium carbonate, calcium carbonate, barium sulfate, barium carbonate, magnesium bicarbonate, calcium bicarbonate, lithium carbonate, calcium phosphate, titanium phosphate, silver chloride, and silver bromide, and other metal salts; magnesium hydroxide, aluminum hydroxide, calcium hydroxide, and other metal hydroxides; titanium, iron, chromium, nickel, gold, silver, platinum, copper, lead, zinc, and other metals and alloys thereof; diamond; boron nitride, boron carbide, and other boron-containing compounds; titanium carbide, tantalum carbide, and zirconium carbide, and other metal nitrides; aluminum nitride, titanium nitride, and other metal nitrides; and mixtures of magnesium aluminometasilicate (magnesium aluminometasilicate), and other particles containing one or more inorganic substances. These inorganic particles can be used alone or in combination of two or more kinds. The inorganic particles may be either non-surface-treated or surface-treated. The content of the inorganic substance in the inorganic particles is preferably 60% by mass or more, more preferably 70% by mass or more, and preferably 100% by mass or less. In addition, when the inorganic particles are surface-treated, the mass and average particle diameter D B is the mass including the surface treatment agent, and the average particle diameter D B means...

[0024] When component (B) is an inorganic particle, from the viewpoint of providing a good feel after application to the skin, component (B) is preferably a particle containing one or more selected from a silicon-containing compound, a metal oxide, a metal salt, a metal nitride, and a metal carbide, more preferably a particle containing one or more selected from a silicon-containing compound and a metal oxide, even more preferably a particle containing one or more selected from silica, calcium silicate, titanium oxide, zinc oxide, and magnesium aluminometasilicate, still more preferably a particle containing one or more selected from silica and calcium silicate, and even more preferably a silica particle containing silica.

[0025] From the viewpoint of improving the feel after application to the skin, the organic particles preferably contain at least one selected from natural polymers, semi-synthetic polymers, and synthetic polymers.Specific examples include polysaccharides such as cellulose, starch, chitosan, and derivatives thereof; addition polymerization polymers such as polystyrene, poly(meth)acrylate, polyvinyl acetate, polyethylene, polypropylene, and other polyolefins; condensation polymers such as polyesters such as polyamide and polylactic acid, and polyurethane; and silicone powder.The polymer particles may be polymer particles having a crosslinked structure or may not have a crosslinked structure. Among these, from the same viewpoint as above, preferred are particles containing one or more selected from polystyrene, poly(meth)acrylate, polyamide, polylactic acid, silicone powder, cellulose, cellulose derivatives, starch, and starch derivatives, more preferred are particles containing one or more selected from polystyrene, poly(meth)acrylate, cellulose, and cellulose derivatives, and from the viewpoint of versatility, even more preferred are poly(meth)acrylate particles containing poly(meth)acrylate. In this specification, "(meth)acrylate" means one or more selected from acrylate and methacrylate.

[0026] The poly(meth)acrylate may be a homopolymer or copolymer of a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include (meth)acrylic acid and (meth)acrylates such as (meth)acrylates having a hydrocarbon group derived from an aliphatic alcohol having 1 to 18 carbon atoms. The (meth)acrylic monomer may be used alone or in combination of two or more. In this specification, "(meth)acrylic acid" means one or more selected from acrylic acid and methacrylic acid. The poly(meth)acrylate may be a poly(meth)acrylate having a crosslinked structure obtained by further copolymerizing a polyfunctional (meth)acrylate such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, or hexanediol di(meth)acrylate in addition to (meth)acrylic acid and (meth)acrylate.

[0027] Specific examples of the poly(meth)acrylate include polymethyl methacrylate and acrylic acid / methyl acrylate copolymer, and examples of the (poly)acrylate having a crosslinked structure include butyl acrylate / ethylene glycol dimethacrylate / sodium methacrylate copolymer and lauryl methacrylate / ethylene glycol dimethacrylate / sodium methacrylate copolymer. Examples of the poly(meth)acrylate particles include particles described as "crosslinked (meth)acrylic acid ester resin particles" in JP-A-2006-8980, the Ganz Pearl series by Aica Kogyo Co., Ltd., and the like.

[0028] The component (B) may be in the form of primary particles, or may be in the form of aggregates of primary particles. The particle may be in a form including solid bodies (secondary particles). The particle structure of component (B) may be non-porous particles, porous particles, composite particles consisting of a core particle and fine particles covering the surface of the core particle, etc. In the present invention, the term "non-porous particles" refers to particles having a specific surface area of ​​50 m 2 / g or less, and "porous particles" are particles with a specific surface area of ​​50 m2 The specific surface area can be measured in accordance with JIS Z 8830:2013. From the viewpoint of improving the adhesion-inhibiting effect and improving the feel after application to the skin, the component (B) is preferably at least one selected from composite particles (B1) in which at least a portion of the surface of core particles (b1-1) is covered with inorganic fine particles (b1-2), and porous particles (B2).

[0029] (Composite particle (B1)) The composite particles (B1) are particles in which at least a part of the surface of a core particle (b1-1) is covered with inorganic fine particles (b1-2). The core particle (b1-1) may be either a non-porous particle or a porous particle. The average particle size of the core particles (b1-1) is preferably 1 μm or more, more preferably 2 μm or more, even more preferably 3 μm or more, and is preferably 10 μm or less, more preferably 9 μm or less, even more preferably 8 μm or less. The average particle size of the core particles (b1-1) can be measured by the method described in the Examples. The core particles (b1-1) may be any of the above-mentioned organic particles and inorganic particles. Among them, from the viewpoint of improving the adhesion suppression effect and improving the feel after application to the skin, one or more selected from poly(meth)acrylate particles and silica particles are preferred. Commercially available core particles (b1-1) include particles described as "crosslinked (meth)acrylic acid ester resin particles" in JP 2006-8980 A, poly(meth)acrylate particles such as the Ganz Pearl series from Aica Kogyo Co., Ltd., and silica particles such as "NP-100" from AGC Si-Tech Co., Ltd.

[0030] From the viewpoint of the productivity of the composite particle, the core particle (b1-1) is preferably one whose surface is coated with a binder (c). This allows the composite particle (B1) to have a structure in which the inorganic fine particles (b1-2) are adsorbed to the core particle (b1-1) via the binder (c). The binder (c) is preferably one having a functional group capable of generating an interaction with the surface hydroxyl group of the inorganic fine particles (b1-2), and more preferably a polymer having an amide bond or an amide group in the side chain. By using a polymer having an amide bond or an amide group in the side chain as the binder (c), a structure in which the inorganic fine particles (b1-2) are adsorbed to the surface of the core particle (b1-1) via hydrogen bonds can be formed. From the same viewpoint as above, the binder (c) is preferably one or more selected from a vinyl polymer obtained by addition polymerization of a vinyl monomer having an amide bond or an amide group, and a homopolymer or copolymer of an oxazoline, more preferably one or more selected from poly(N-vinylpyrrolidone), poly(meth)acrylamide, and a homopolymer or copolymer of an oxazoline, and even more preferably one or more selected from poly(N-vinylpyrrolidone), and a homopolymer or copolymer of an oxazoline. In this specification, "(meth)acrylamide" means one or more selected from acrylamide and methacrylamide.

[0031] Examples of the vinyl monomer constituting the vinyl polymer include N-vinyl compounds such as N-vinylpyrrolidone, N-vinylacetamide, N-vinylformamide, and N-vinylcaprolactam; (meth)acrylamide monomers such as (meth)methacrylamide and N-alkyl(meth)acrylamide. Among these, one or more selected from poly(N-vinylpyrrolidone) and poly(meth)acrylamide are preferred, and poly(N-vinylpyrrolidone) is more preferred. The poly(N-vinylpyrrolidone) may be an N-vinylpyrrolidone homopolymer, an N-vinylpyrrolidone / vinyl acetate copolymer, an N-vinylpyrrolidone / vinyl acetate / vinyl propionate copolymer, or another copolymer of N-vinylpyrrolidone and another monomer. Commercially available poly(N-vinylpyrrolidone) may be, for example, PVP K-90 (manufactured by Ashland Specialty Ingredients), PVP K-25, PVP K-30, and PVP K-90 (trade names, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.); PVA-6450 and Acorn M (trade names, manufactured by Osaka Organic Chemical Industry Co., Ltd.); and Kollidon VA64 (trade name, vinylpyrrolidone / vinyl acetate copolymer, manufactured by BASF Japan Ltd.). The poly(meth)acrylamide may be a homopolymer of a (meth)acrylic monomer, a copolymer of a (meth)acrylic monomer with another monomer such as a (meth)acrylate or (meth)acrylic acid, or a salt thereof. An example of the poly(meth)acrylamide is an N-tert-butylacrylamide / N,N-dimethylacrylamide / N-[3-(dimethylamino)propyl]acrylamide / methoxypolyethylene glycol methacrylate copolymer described in JP-A-2005-162700.

[0032] As the homopolymer or copolymer of oxazolines, from the viewpoint of providing a good feel after application to the skin, a copolymer of oxazolines is preferred, and an oxazoline-modified silicone having a poly(N-acylalkyleneimine) chain at its side chain, which is formed by ring-opening polymerization of a cyclic iminoether, is more preferred. Examples of oxazoline-modified silicones include poly(N-formylethyleneimine) organopolysiloxane copolymers, poly(N-acetylethyleneimine) organopolysiloxane copolymers, and poly(N-propionylethyleneimine) / organopolysiloxane copolymers, such as poly(N-acylalkyleneimine) / organopolysiloxane copolymers. Among these, poly(N-propionylethyleneimine) / methylpolysiloxane copolymer (POLYSILICONE-9) is preferred. The poly(N-acylalkyleneimine) / organopolysiloxane copolymer can be obtained, for example, by reacting poly(N-acylalkyleneimine), which is a ring-opening polymer of cyclic iminoether, with organopolysiloxane forming a main chain segment. For example, POLYSILICONE-9 described in JP-A-2016-6029 can be used.

[0033] The average primary particle size of the inorganic fine particles (b1-2) is preferably 1 nm or more, more preferably 2 nm or more, even more preferably 3 nm or more, and is preferably 30 nm or less, more preferably 25 nm or less, even more preferably 20 mm or less. The average primary particle size of the inorganic fine particles (b1-2) can be measured by the method described in the Examples. Examples of the inorganic fine particles (b1-2) include the inorganic particles described above. When a metal oxide is used as the inorganic fine particles (b1-2), the surface of the metal oxide is preferably subjected to a hydrophilization treatment. Examples of hydrophilization treatments include treatments with silica, hydrous silica, hydrous oxides, oxides or hydroxides of metals such as aluminum and zirconia, water-soluble polymers such as polyacrylic acid, alginic acid or salts thereof, etc. Among these, one or more treatments selected from silica treatment, hydrous silica treatment and aluminum hydroxide treatment are preferred. The amount of the hydrophilization treatment on the inorganic fine particles (b1-2) is preferably 0.1% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, based on the inorganic fine particles (b1-2).

[0034] From the viewpoints of improving the adhesion suppression effect while providing a good feel after application to the skin, the inorganic fine particles (b1-2) are preferably one or more selected from silicon-containing compounds and metal oxides, more preferably one or more selected from hydrophilic silica and metal oxides treated to be hydrophilized, even more preferably one or more selected from hydrophilic silica, titanium oxide and zinc oxide surface-treated with one or more selected from silica, hydrous silica and aluminum hydroxide, and even more preferably one or more selected from titanium oxide and zinc oxide surface-treated with one or more selected from silica, hydrous silica and aluminum hydroxide. Commercially available inorganic microparticles (b1-2) include "MT-100WP" (hydrated silica-treated titanium oxide microparticles) manufactured by Teika Co., Ltd., "STR-100W" (hydrated silica-treated titanium oxide microparticles), "STR-100C" (aluminum hydroxide-treated titanium oxide microparticles), and "FINEX-33W" (hydrated silica-treated zinc oxide microparticles) manufactured by Sakai Chemical Industry Co., Ltd., and "AEROSIL200" (hydrophilic silica microparticles) manufactured by Evonik.

[0035] The composite particles (B1) are preferably produced by mixing the core particles (b1-1) and the inorganic fine particles (b1-2). This allows the core particles (b1-1) having a large average particle size to form a hetero-aggregation with the inorganic fine particles (b1-2) having a small average primary particle size, resulting in a structure in which at least a part of the surface of the core particles (b1-1) is covered with the inorganic fine particles (b1-2). The mixing method is not particularly limited, and may be a method of adding inorganic fine particles (b1-2) to a dispersion liquid of core particles (b1-1). The dispersion medium of core particles (b1-1) is not particularly limited, and may be, for example, a lower alcohol such as ethanol, water, etc. When using particles whose surfaces are coated with a binder (c) as the core particles (b1-1), it is preferable to use particles obtained by previously mixing the particles constituting the core particles (b1-1) with the binder (c).

[0036] From the viewpoint of productivity of the composite particles, the amount of the binder (c) to be blended with the core particles (b1-1) is preferably 0.01 mass % or more, more preferably 0.03 mass % or more, even more preferably 0.05 mass % or more, and is preferably 3 mass % or less, more preferably 1 mass % or less, even more preferably 0.5 mass % or less. From the viewpoint of the productivity of the composite particles, the blending amount of the inorganic fine particles (b1-2) relative to the core particles (b1-1) is preferably 0.05 mass % or more, more preferably 0.15 mass % or more, even more preferably 0.25 mass % or more, and is preferably 10 mass % or less, more preferably 3 mass % or less, even more preferably 1 mass % or less.

[0037] (Porous particles (B2)) The porous particles (B2) are preferably aggregates of inorganic fine particles (b2) having an average primary particle diameter of 1 nm or more and 30 nm or less. The inorganic fine particles (b2) may be the same as the inorganic particles described above. Among them, from the viewpoint of improving the feel after application and the feeling of use of the topical agent, particles containing one or more selected from silicon-containing compounds and metal oxides are preferred, and particles containing one or more selected from silica and titanium oxide are more preferred. The average primary particle size of the porous particles (B2) can be measured by the method described in the Examples. Commercially available porous particles (B2) include "Sunsphere H-51" (porous silica particles) manufactured by AGC Si-Tech Co., Ltd.; and "HCS Refre 50" (aggregate of silica and titanium oxide) manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0038] In addition to components (A) and (B), the topical preparation may appropriately contain cosmetic ingredients or medicinal ingredients used according to the purpose of the topical preparation, or ingredients normally used in topical preparations such as skin cosmetics, within the scope of the present invention. Examples of such ingredients include oils, solvents, antioxidants, UV absorbers, surfactants, thickeners, emulsifiers, neutralizing agents, pH adjusters, bactericides, anti-inflammatory agents, preservatives, colorants, chelating agents, moisturizing agents, pearling agents, ceramides, antiperspirants, fragrances, etc.

[0039] [Production of topical preparations] The topical preparation used in the present invention can be produced by appropriately using a known method depending on the formulation of the topical preparation. For example, a method of blending component (A), component (B), and, if necessary, other components described above, and stirring and mixing them with a disperser or the like can be mentioned. When the topical preparation is a water-in-oil (W / O) type or an oil-in-water (O / W) type described later, a method of preparing an aqueous phase and an oil phase separately and then mixing the two can be used. The contents and mass ratios of each component are as follows.

[0040] (Content of ingredient (A) in topical preparation) The content of component (A) in the topical preparation is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass or more from the viewpoint of improving the adhesion-inhibiting effect, and is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less from the viewpoint of improving the feel after application to the skin and from the viewpoint of economy. More specifically, the content of component (A) is preferably 1 to 40% by mass, more preferably 1.5 to 20% by mass, even more preferably 1.5 to 10% by mass, and even more preferably 2 to 10% by mass from the viewpoint of improving the adhesion-inhibiting effect, improving the feel after application to the skin, and improving the feeling when using the topical preparation.

[0041] (Content of ingredient (B) in topical preparation) The content of component (B) in the topical preparation is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more from the viewpoint of providing a good feel after application to the skin, and is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less from the viewpoint of improving the adhesion inhibitory effect.

[0042] (Mass ratio [(A) / (B)]) The mass ratio [(A) / (B)] of the content of component (A) to the content of component (B) in the topical agent is 0.30 or more, preferably 0.32 or more, more preferably 0.35 or more, even more preferably 0.40 or more, even more preferably 0.60 or more, even more preferably 0.80 or more, and from the viewpoint of improving the adhesion-inhibiting effect, it is 5.0 or less, preferably 4.5 or less, more preferably 4.0 or less, even more preferably 3.5 or less, even more preferably 3.0 or less, even more preferably 2.5 or less. More specifically, the mass ratio [(A) / (B)] is preferably 0.32 to 4.5, more preferably 0.35 to 4.0, even more preferably 0.40 to 3.5, even more preferably 0.60 to 3.0, even more preferably 0.80 to 2.5, from the viewpoint of improving the adhesion-inhibiting effect and from the viewpoint of improving the feel after application to the skin.

[0043] When the topical preparation further contains an oil, the content of the oil in the topical preparation is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 7% by mass or more, from the viewpoint of improving the adhesion inhibitory effect and of providing a good feel after application to the skin, and is preferably 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less.

[0044] The form of the topical agent used in the present invention may be an aqueous type having a single aqueous phase as the dispersion medium, an oil-based type having a single oil phase as the dispersion medium, an oil-in-water type (hereinafter also referred to as "O / W type"), a water-in-oil type (hereinafter also referred to as "W / O type"), etc., and may be appropriately selected. In the present invention, the topical preparation can be applied, for example, as a topical preparation to be applied to the skin or hair. From the viewpoint of adhesion suppression effect, the topical preparation is preferably a cosmetic preparation, more preferably a skin cosmetic preparation. The dosage form of the external preparation is not particularly limited, and it may be in any dosage form, such as liquid, foam, paste, cream, or solid.

[0045] [Coating method] In the present invention, the method of applying the topical agent to the skin can be a known method depending on the form or purpose of use of the topical agent. Here, "applying to the skin" includes not only directly applying the topical agent to the skin surface with the hands, etc., but also attaching the topical agent to the skin surface by spraying, etc. The topical agent in the form of a liquid, foam, paste, cream, or solid can usually be applied as it is by applying, spraying, etc.

[0046] (Amount of component (A) applied) The amount of component (A) applied to the skin surface is preferably 0.01 mg / cm from the viewpoint of improving the adhesion suppression effect. 2 More preferably, 0.02 mg / cm 2 More preferably, 0.03 mg / cm 2 More preferably, 0.04 mg / cm 2 From the viewpoint of providing a good feel after application to the skin and from the viewpoint of economy, the amount is preferably 0.8 mg / cm 2 Less than 0.7 mg / cm, more preferably 0.7 mg / cm 2 More specifically, the amount of component (A) applied to the skin surface is preferably 0.01 to 0.8 mg / cm from the viewpoint of improving the adhesion suppression effect, from the viewpoint of improving the feel after application to the skin, and from the viewpoint of economy. 2 , more preferably 0.02 to 0.8 mg / cm 2 , and more preferably 0.03 to 0.8 mg / cm 2 , and even more preferably 0.04 to 0.8 mg / cm 2 , and even more preferably 0.04 to 0.7 mg / cm 2 It is.

[0047] When the topical preparation is a W / O type, the amount of component (A) applied to the skin surface is preferably 0.01 mg / cm from the viewpoint of improving the adhesion suppression effect. 2 More preferably, 0.02 mg / cm 2 More preferably, 0.03 mg / cm 2 More preferably, 0.04 mg / cm 2From the viewpoint of providing a good feeling when applied to the skin and from the viewpoint of economy, the amount is preferably 0.8 mg / cm 2 Less than 0.7 mg / cm, more preferably 0.7 mg / cm 2 More specifically, the amount of component (A) applied to the skin surface is preferably 0.01 to 0.8 mg / cm from the viewpoint of improving the adhesion suppression effect, from the viewpoint of improving the feel after application to the skin, and from the viewpoint of economy. 2 , more preferably 0.02 to 0.8 mg / cm 2 , and more preferably 0.03 to 0.8 mg / cm 2 , and even more preferably 0.04 to 0.8 mg / cm 2 , and even more preferably 0.04 to 0.7 mg / cm 2 It is.

[0048] When the topical preparation is an O / W type, the amount of component (A) applied to the skin surface is preferably 0.01 mg / cm from the viewpoint of improving the adhesion suppression effect. 2 More preferably, 0.02 mg / cm 2 More preferably, 0.03 mg / cm 2 More preferably, 0.04 mg / cm 2 From the viewpoint of providing a good feel after application to the skin and from the viewpoint of economy, the amount is preferably 0.8 mg / cm 2 Less than 0.7 mg / cm, more preferably 0.7 mg / cm 2 More preferably, 0.5 mg / cm 2 More preferably, 0.3 mg / cm or less. 2 More specifically, the amount of component (A) applied to the skin surface is preferably 0.01 to 0.8 mg / cm from the viewpoint of improving the adhesion suppression effect, from the viewpoint of improving the feel after application to the skin, and from the viewpoint of economy. 2 , more preferably 0.02 to 0.8 mg / cm 2 , and more preferably 0.03 to 0.8 mg / cm 2 , and even more preferably 0.04 to 0.7 mg / cm 2 , and even more preferably 0.04 to 0.5 mg / cm 2, and even more preferably 0.04 to 0.3 mg / cm 2 It is.

[0049] In addition to the above-mentioned embodiment, the present invention further discloses the following embodiments. <1> A method for suppressing adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, the method comprising: The topical preparation contains the following components (A) and (B), and the mass ratio of the content of component (A) to the content of component (B) in the topical preparation [(A) / (B)] is 0.32 or more and 4.5 or less. Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​1 nm or more and 80 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less <2> A method for suppressing adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, the method comprising: The topical preparation contains the following components (A) and (B), and the mass ratio of the content of component (A) to the content of component (B) in the topical preparation [(A) / (B)] is 0.32 or more and 4.5 or less. Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​5 nm or more and 50 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 3 μm or more and 8 μm or less <3> The mass ratio [(A) / (B)] of the content of the component (A) to the content of the component (B) in the topical preparation is 0.40 or more and 3.5 or less. <1> or <2> 2. A method for suppressing adhesion of harmful air substances according to claim 1. <4> The mass ratio [(A) / (B)] of the content of the component (A) to the content of the component (B) in the topical preparation is 0.80 or more and 2.5 or less. <1> or <2> 2. A method for suppressing adhesion of harmful air substances according to claim 1.

[0050] <5> The amount of component (A) applied to the skin is 0.03 mg / cm 2More than 0.8mg / cm 2 The above-mentioned <1> ~ <4> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <6> The topical agent is an oil-in-water type (O / W type), and the amount of component (A) applied to the skin is 0.04 mg / cm 2 More than 0.3mg / cm 2 The above-mentioned <1> ~ <4> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <7> The content of the component (A) in the topical preparation is 1% by mass or more and 40% by mass or less. <1> ~ <6> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <8> The content of the component (A) in the topical preparation is 1.5% by mass or more and 20% by mass or less. <1> ~ <6> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <9> The content of the component (A) in the topical preparation is 2% by mass or more and 10% by mass or less. <1> ~ <6> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11.

[0051] <10> A method for suppressing adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, the method comprising: The topical preparation contains the following components (A) and (B), the mass ratio of the content of component (A) to the content of component (B) in the topical preparation [(A) / (B)] is 0.40 or more and 3.5 or less, and the amount of component (A) applied to the skin is 0.03 mg / cm 2 More than 0.8mg / cm 2 The method for suppressing adhesion of harmful substances to the air is as follows. Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​1 nm or more and 80 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less <11> A method for inhibiting adhesion of atmospheric hazardous substances to the skin by applying an oil-in-water (O / W) type topical preparation to the skin, the method comprising: The topical preparation contains the following components (A) and (B), the mass ratio of the content of component (A) to the content of component (B) in the topical preparation [(A) / (B)] is 0.80 or more and 2.5 or less, and the amount of component (A) applied to the skin is 0.04 mg / cm 2 More than 0.3mg / cm 2 The method for suppressing adhesion of harmful substances to the air is as follows. Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​5 nm or more and 50 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 3 μm or more and 8 μm or less

[0052] <12> A method for suppressing adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, the method comprising: The topical preparation contains the following components (A) and (B), the mass ratio of the content of component (A) to the content of component (B) in the topical preparation [(A) / (B)] is 0.40 or more and 3.5 or less, and the content of component (A) in the topical preparation is 1% by mass or more and 40% by mass or less. Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​1 nm or more and 80 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less <13> A method for suppressing adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, the method comprising: The topical preparation contains the following components (A) and (B), the mass ratio of the content of component (A) to the content of component (B) in the topical preparation [(A) / (B)] is 0.80 or more and 2.5 or less, and the content of component (A) in the topical preparation is 2% by mass or more and 10% by mass or less. Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​5 nm or more and 50 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 3 μm or more and 8 μm or less

[0053] <14> The component (B) is at least one selected from composite particles (B1) in which at least a part of the surface of a core particle (b1-1) is covered with inorganic fine particles (b1-2), and porous particles (B2). <1> ~ <13> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of claims 1 to 11. <15> The core particles (b1-1) constituting the composite particles (B1) are one or more particles selected from poly(meth)acrylate particles and silica particles. <14> 2. A method for suppressing adhesion of harmful air substances according to claim 1. <16> The surface of the core particle (b1-1) constituting the composite particle (B1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines. <14> or <15> 2. A method for suppressing adhesion of harmful air substances according to claim 1. <17> The inorganic fine particles (b1-2) constituting the composite particles (B1) are one or more selected from titanium oxide and zinc oxide, the surface of which is treated with one or more selected from silica, hydrated silica, and aluminum hydroxide. <14> ~ <16> 2. A method for inhibiting adhesion of atmospheric hazardous substances according to any one of the preceding claims.

[0054] <18> The following components (A) and (B): Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​1 nm or more and 80 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less Contains The component (B) is a composite particle (B1) in which at least a part of the surface of a core particle (b1-1) is coated with inorganic fine particles (b1-2), the core particles (b1-1) are one or more particles selected from poly(meth)acrylate particles and silica particles; the surface of the core particle (b1-1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines; the inorganic fine particles (b1-2) are one or more selected from titanium oxide and zinc oxide that have been surface-treated with one or more selected from silica, hydrous silica, and aluminum hydroxide; A topical preparation, in which the mass ratio of the content of component (A) to the content of component (B) [(A) / (B)] is 0.32 or more and 4.5 or less.

[0055] <19> The following components (A) and (B): Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​5 nm or more and 50 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 3 μm or more and 8 μm or less Contains The component (B) is a composite particle (B1) in which at least a part of the surface of a core particle (b1-1) is coated with inorganic fine particles (b1-2), the core particles (b1-1) are one or more particles selected from poly(meth)acrylate particles and silica particles; the surface of the core particle (b1-1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines; the inorganic fine particles (b1-2) are one or more selected from titanium oxide and zinc oxide that have been surface-treated with one or more selected from silica, hydrous silica, and aluminum hydroxide; A topical preparation, in which the mass ratio of the content of component (A) to the content of component (B) [(A) / (B)] is 0.32 or more and 4.5 or less.

[0056] <20> The mass ratio [(A) / (B)] of the content of the component (A) to the content of the component (B) in the topical preparation is 0.40 or more and 3.5 or less. <18> or <19> 2. The topical preparation according to claim 1 . <21> The mass ratio [(A) / (B)] of the content of the component (A) to the content of the component (B) in the topical preparation is 0.80 or more and 2.5 or less. <18> or <19> 2. The topical preparation according to claim 1 . <22> The content of the component (A) in the topical preparation is 1% by mass or more and 40% by mass or less. <18> ~ <21> 2. The topical preparation according to claim 1 . <23> The content of the component (A) in the topical preparation is 1.5% by mass or more and 20% by mass or less. <18> ~ <21> 2. The topical preparation according to claim 1 . <24> The content of the component (A) in the topical preparation is 2% by mass or more and 10% by mass or less. <18> ~ <21> 2. The topical preparation according to claim 1 .

[0057] <25> The following components (A) and (B): Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​1 nm or more and 80 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 1 μm or more and 10 μm or less An external preparation containing The component (B) is a composite particle (B1) in which at least a part of the surface of a core particle (b1-1) is coated with inorganic fine particles (b1-2), the core particles (b1-1) are one or more particles selected from poly(meth)acrylate particles and silica particles; the surface of the core particle (b1-1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines; the inorganic fine particles (b1-2) are one or more selected from titanium oxide and zinc oxide that have been surface-treated with one or more selected from silica, hydrous silica, and aluminum hydroxide; The mass ratio [(A) / (B)] of the content of component (A) to the content of component (B) in the topical preparation is 0.40 or more and 3.5 or less, and the content of component (A) in the topical preparation is 1% by mass or more and 40% by mass or less.

[0058] <26> The following components (A) and (B): Component (A): Average primary particle diameter d A One or more selected from titanium oxide and zinc oxide, each having a surface area of ​​5 nm or more and 50 nm or less. Component (B): Average particle diameter D B Non-disintegrating particles with a size of 3 μm or more and 8 μm or less An external preparation containing The component (B) is a composite particle (B1) in which at least a part of the surface of a core particle (b1-1) is coated with inorganic fine particles (b1-2), the core particles (b1-1) are one or more particles selected from poly(meth)acrylate particles and silica particles; the surface of the core particle (b1-1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines; the inorganic fine particles (b1-2) are one or more selected from titanium oxide and zinc oxide that have been surface-treated with one or more selected from silica, hydrous silica, and aluminum hydroxide; The mass ratio [(A) / (B)] of the content of component (A) to the content of component (B) in the topical preparation is 0.80 or more and 2.5 or less, and the content of component (A) in the topical preparation is 2% by mass or more and 10% by mass or less. EXAMPLES

[0059] In the following examples and comparative examples, "parts" and "%" are "parts by mass" and "% by mass" unless otherwise specified.

[0060] (1) Average primary particle diameter d of component (A) A , the average primary particle diameter of the inorganic fine particles (b1-2) and the porous particles (B2) When the measurement sample has a shape other than a plate shape, a dispersion of the measurement sample prepared in advance is placed on the sample stage of a transmission electron microscope (TEM) (trade name "JEM1400Plus", manufactured by JEOL Ltd.) and air-dried, and the maximum short diameters of 300 primary particles in an image observed under conditions of observation magnification of 50,000 times with the TEM are measured, and the number average value is taken as the average primary particle diameter. Here, the maximum short diameter means the short diameter having the greatest length among the short diameters perpendicular to the long diameter. When the measurement sample had a plate-like shape, the thicknesses of 300 primary particles in an image observed under the same method and magnification conditions as above were measured, and the number average value was taken as the average primary particle diameter for each. The dispersion of the measurement sample was prepared by adding 95 g of ethanol as a solvent to 5 g of the measurement sample and subjecting the mixture to ultrasonic dispersion.

[0061] (2) Average particle size D of component (B) B , the average particle size of the core particles (b1-1) Measurements were performed using a laser diffraction / scattering type particle size distribution analyzer (product name "LA-920", manufactured by Horiba, Ltd.) with ion-exchanged water as the dispersion medium. The relative refractive index was set to 1.10 for organic particles and 1.09 for inorganic particles. Measurements were performed using a flow cell under the following measurement conditions: circulation speed: 15, ultrasonic irradiation: none, distribution form: standard, particle size standard: volume.

[0062] (3) Check for collapsibility 0.04 g of each particle dispersion (dispersion medium: ethanol, solid content concentration: 5%) was spread evenly over an artificial leather (product name "Laforet S2923", manufactured by Okamoto Shinwa Co., Ltd.) (5 cm x 4 cm) for 20 seconds (particle adhesion amount: 0.1 mg / cm 2), and dried at room temperature for 24 hours to obtain each measurement sample. Using a surface property measuring device (trade name "Tribogear TYPE: 14", manufactured by Shinto Scientific Co., Ltd.) (vertical load: 360 g, movement distance: 50 mm, movement speed: 600 mm / min), a jig (3 cm x 3 cm) with uncoated artificial leather (Laforet S2923) (3 cm x 10 cm) attached was used to rub the particle-coated surface of the measurement sample back and forth 10 times. Next, the rubbed surface of the measurement sample was observed at a magnification of 15,000 times using a field emission scanning electron microscope (FE-SEM-4800 (5.0 kV)) (manufactured by Hitachi High-Tech Co., Ltd.), and the major and minor diameters of 30 particles in the observed image were measured, and the average value of the major and minor diameters was taken as the particle diameter of each particle. The volume-based particle diameter was calculated from the particle diameters of the 30 particles, and the average particle diameter D after rubbing was calculated. B ' Average particle size after scraping D B ' and the average particle diameter D before rubbing measured in (2) above B Using the above formula, particles with a particle size ratio of less than 50% represented by the following formula (I) were defined as "easily disintegrating particles", and particles with a particle size ratio of 50% or more represented by the following formula (I) were defined as "non-disintegrating particles". Particle size ratio before and after scraping (%) = (average particle size after scraping D B ' / Average particle size before abrasion D B )×100 (I)

[0063] (Production of polymethacrylate particles P1) Manufacturing Example 1 Polymethacrylate particles P1 (particles of lauryl methacrylate / ethylene glycol dimethacrylate / sodium methacrylate copolymer) were synthesized according to Example 1 of JP 2006-8980 A. The average particle size of the polymethacrylate particles P1 was 3 μm.

[0064] (Preparation of Composite Particles (B1)) Preparation Example 1 As the core particle (b1-1), 100g of the polymethacrylate particle P1 obtained in Production Example 1 was dispersed in 150g of purified water, and 0.1g of oxazoline-modified silicone (trade name "OS-50TE-E", manufactured by Kao Corporation) was added, followed by stirring for 1 hour to obtain coated polymethacrylate particle P1-1 (hereinafter also referred to as "coated polymethacrylate particle P1-1") coated with oxazoline-modified silicone. Next, 0.5g of hydrated silica-treated titanium oxide fine particles shown in Table 1 was added as inorganic fine particles (b1-2), followed by stirring for 30 minutes to obtain composite particle B1-1. The composite particle B1-1 was used unpurified in the topical agent described below.

[0065] Preparation Example 2 As the core particles (b1-1), coated polymethacrylate particles P1-1 coated with oxazoline-modified silicone were obtained in the same manner as in Preparation Example 1, and then 0.5 g of aluminum hydroxide-treated titanium oxide particles shown in Table 1 was added as inorganic fine particles (b1-2) and stirred for 30 minutes to obtain composite particles B1-2. The composite particles B1-2 were used unpurified in the topical agent described below.

[0066] Preparation Example 3 As the core particles (b1-1), 100 g of the polymethacrylate particles P1 obtained in Production Example 1 was dispersed in 150 g of purified water, and 0.1 g of polyvinylpyrrolidone (trade name "PVP K-90", manufactured by Ashland Specialty Ingredients) was added, followed by stirring for 1 hour to obtain coated polymethacrylate particles P1-2 (hereinafter also referred to as "coated polymethacrylate particles P1-2") coated with polyvinylpyrrolidone. Next, 0.5 g of hydrophilic fine silica particles shown in Table 1 was added as inorganic fine particles (b1-2), followed by stirring for 30 minutes to obtain composite particles B1-3. The composite particles B1-3 were used unpurified in the topical agent described below.

[0067] Preparation Example 4 As the core particles (b1-1), 100 g of silica particles P2 (trade name "Sunsphere NP-100", manufactured by AGC Si-Tech Co., Ltd., average particle diameter 10 μm) was dispersed in 150 g of purified water, and 0.1 g of polyvinylpyrrolidone (PVP K-90) was added, followed by stirring for 1 hour to obtain coated silica particles P2-1 (hereinafter also referred to as "coated silica particles P2-1") coated with polyvinylpyrrolidone. Next, 0.5 g of hydrophilic fine silica particles shown in Table 1 was added as inorganic fine particles (b1-2), followed by stirring for 30 minutes to obtain composite particles B1-4. The composite particles B1-4 were used unpurified in the topical agent described below.

[0068] Preparation Example 5 As the core particles (b1-1), coated polymethacrylate particles P1-1 coated with oxazoline-modified silicone were obtained in the same manner as in Preparation Example 1, and then 0.5 g of hydrated silica-treated zinc oxide particles shown in Table 1 was added as inorganic fine particles (b1-2) and stirred for 30 minutes to obtain composite particles B1-5. The composite particles B1-5 were used unpurified in the topical preparation described below.

[0069] Preparation Example 6 As the core particles (b1-1), 100 g of silica particles P3 (trade name "Sciqas", manufactured by Sakai Chemical Industry Co., Ltd., surface untreated product, average particle diameter 0.4 μm) was dispersed in 150 g of purified water, 0.1 g of polyvinylpyrrolidone (PVP K-90) was added, and the mixture was stirred for 1 hour to obtain coated silica particles P3-1 (hereinafter also referred to as "coated silica particles P3-1") coated with polyvinylpyrrolidone. Next, 0.5 g of hydrophilic fine silica particles shown in Table 1 was added as inorganic fine particles (b1-2), and the mixture was stirred for 30 minutes to obtain composite particles B1'-6. The composite particles B1'-6 were used unpurified in the topical agent described below.

[0070] Preparation Example 7 As the core particle (b1-1), the coated polymethacrylate particle P1-2 coated with polyvinylpyrrolidone was obtained in the same manner as in Preparation Example 3, and then 0.5 g of hydrous silica-treated titanium oxide fine particles were added as the inorganic fine particles (b1-2), and the mixture was stirred for 30 minutes to obtain the composite particle B1-7. The composite particle B1-7 was used unpurified in the external preparation described below.

[0071] [Table 1]

[0072] Examples 1 to 12, Comparative Examples 1 to 7 At 25° C., component (B) or component (B'), a thickener, an emulsifier, and a solvent were added to a blending vessel containing water with stirring to prepare an aqueous phase according to the composition shown in Tables 2 to 4. Separately, at 80° C., component (A) and an oil were mixed to prepare an oil phase. The oil phase and neutralizer were then added to the aqueous phase and stirred to obtain topical preparations having the compositions shown in Tables 2 to 4. The obtained topical preparations were evaluated for their effect of inhibiting adhesion of atmospheric hazardous substances and for their feel to the touch by the methods described below. The results are shown in Tables 2 to 4.

[0073] The notations in Tables 2 to 4 are as follows: Average primary particle diameter d of component (A) A and the average particle size D of component (B) or component (B'). B The disintegrability of the particles is shown in Tables 2 to 4. Stearic acid-treated titanium dioxide microparticles A1: Product name "MT-100TV", manufactured by Teika Co., Ltd., spindle-shaped titanium dioxide microparticles treated with stearic acid Octyltriethoxysilane-treated zinc oxide microparticles A2: "FINEX-30-OTS", manufactured by Sakai Chemical Industry Co., Ltd., spherical zinc oxide microparticles treated with octyltriethoxysilane Porous particle B2-1: Product name "HCS Refre 50", JGC Catalysts and Chemicals Co., Ltd., aggregates of 160 nm silica and 250 nm titanium dioxide (silica:titanium dioxide = 50:50), oil absorption 50 mL / 100 g Porous particles B2-2: Product name "Sunsphere H-51", manufactured by AGC Si-Tech Co., Ltd., specific surface area 800 m 2 / g Silica particles P'4: Product name "Sunsphere H-121", manufactured by AGC Si-Tech Co., Ltd. Silica particles P'5: Product name "Sunsphere H-52", manufactured by AGC Si-Tech Co., Ltd. Isopropyl palmitate: Trade name "Excepar IPP", manufactured by Kao Corporation Acrylic acid / alkyl methacrylate copolymer 1: Trade name "PEMULEN TR-1", manufactured by Lubrizol Advanced Materials Acrylic acid / alkyl methacrylate copolymer 2: Trade name "PEMULEN TR-2", manufactured by Lubrizol Advanced Materials

[0074] <Evaluation of the effect of suppressing adhesion of harmful air substances> The topical preparation obtained above was applied to white artificial leather (product name "Laforet S2923", manufactured by Okamoto Shinwa Co., Ltd.) as a skin substitute so as to achieve the application amount of component (A) shown in Tables 2 to 4, and then left to dry overnight at room temperature. The artificial leather surface to which the topical agent was applied was exposed to an airflow environment containing the harmful air substances to be evaluated, and the L * a * b * The value was measured, and the color difference ΔE before and after exposure was measured by the following method. [Measurement of color difference ΔE] Using a colorimeter (product name "CM-2002", manufactured by Konica Minolta, Inc.), the L1 * , a1 * , b1 * The values ​​were measured. Separately, a blower (product name "Silky Wind 9ZF002RH02", size: 129 × 106 × 83 mm, manufactured by Rhythm Watch Co., Ltd.) and a mesh sieve (Test sieves JIS Z 8801, frame dimensions: φ100 × 45H, mesh size: 106 μm, manufactured by Tokyo Screen Co., Ltd.) were fixed in a glove bag (product number "3-118-01", manufactured by AS ONE Co., Ltd.). The installation height of the mesh sieve was 17 cm. The artificial leather (5 cm x 4 cm) coated with the test sample topical agent was attached to a support so that the height of the lower end of the artificial leather was 11 cm. The distance between the coated surface of the artificial leather on the support and the blower was 15 cm, and the coated surface of the artificial leather was perpendicular to the direction of the air blowing from the blower as shown in Figure 1, and the center height of the blower blades and the center height of the artificial leather were the same. The temperature inside the glove bag was set to 25°C and the relative humidity to 57%RH, and 50 mg of graphite powder (product name "J-CPB", average particle size 5.5 μm, manufactured by Nippon Graphite Industries Co., Ltd.) as the air hazardous substance to be evaluated was classified using a mesh sieve removal brush (product name "JNB-5", brush diameter 53 μm, manufactured by Tokyo Screen Co., Ltd.) and dropped in front of the outlet of a blower with the air blowing scale set to 1 for 1 minute, exposing the artificial leather surface to which the topical agent had been applied to the air blowing environment of the air hazardous substance to be evaluated. Next, the L2 of the exposed artificial leather surface was measured using the above colorimeter. * , a2 * , b2 * The value was measured, and the color difference ΔE value was calculated according to the following formula (II-1). ΔE = [(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2 ] 0.5 (II-1) The above operation was carried out three times for each test sample, and the average value of the color difference ΔE of the artificial leather coated with the topical agent of the test sample was taken as ΔEt. Furthermore, the same operation as above was carried out three times for the artificial leather not coated with the topical agent as a standard sample, and the average value of the color difference ΔE was taken as ΔEs, and the adhesion inhibition rate was calculated from the following formula (II-2). The higher the adhesion inhibition rate, the better the adhesion inhibition effect of air hazardous substances. Air hazardous substance adhesion inhibition rate (%) = 100 × (ΔEs-ΔEt) / ΔEs (II-2)

[0075] <Evaluation of texture (smoothness)> Three expert panelists applied 0.02 mL of each topical agent to the inside of the forearm in a 3 cm diameter circle, and spread it evenly over 20 seconds under conditions of 25°C and 57% RH. The feel (smooth feeling) of the topical agent 15 minutes after application was evaluated on a 5-point scale according to the following criteria, and the average score of the three panelists was calculated. The results are shown in Tables 2 to 4. 5: Feels very smooth. 4: Feels smooth. 3: Does not feel smooth. 2: Feels sticky or squeaky. 1: Extremely sticky and squeaky feeling.

[0076] [Table 2]

[0077] [Table 3]

[0078] [Table 4]

[0079] As shown in Tables 2 to 4, in Examples 1 to 12, the average primary particle diameter d A The metal oxide and component (B) have an average particle diameter D B It can be seen that by applying an external preparation containing a specified mass ratio of non-disintegrating particles having a specified range, a high adhesion suppression effect is achieved and the feel (smooth feeling) after application to the skin is good compared to Comparative Examples 1 to 7.

[0080] Examples 13 and 14 At 25° C., component (B), a thickener, an emulsifier, and a solvent were added to a blending vessel containing water with stirring to prepare an aqueous phase according to the compositions shown in Formulation Examples 1 and 2 in Table 5. Separately, at 80° C., component (A) and an oil were mixed to prepare an oil phase. The oil phase, neutralizer, and other components were then added to the aqueous phase and stirred to obtain an external preparation having the composition shown in Table 5. The obtained topical preparation was evaluated for its effect of inhibiting adhesion of atmospheric hazardous substances and for its feel to the touch by the methods described above. The results are shown in Table 5. In Table 5, the components other than those shown in Tables 2 to 4 are represented as follows. The average primary particle diameter d A and the average particle size D of component (B) B The disintegrability of the particles is shown in Table 5. Octyltriethoxysilane-treated titanium dioxide microparticles A3: Product name "STR-100W-OTS", manufactured by Sakai Chemical Industry Co., Ltd., spindle-shaped titanium dioxide microparticles treated with octyltriethoxysilane *1: Product name: "Ubinal MC80", manufactured by BASF Japan Ltd. *2: Product name: "Ubinal T-150", manufactured by BASF Japan Ltd. *3: Product name: "TINOSORB S", manufactured by BASF Japan Ltd. *4: Product name: "Pearlream EX", manufactured by NOF Corporation *5: Product name: "KF-96A-10CS", manufactured by Shin-Etsu Chemical Co., Ltd. *6: Product name: "Cetyl Alcohol NX", manufactured by Kokyu Alcohol Kogyo Co., Ltd.

[0081] [Table 5]

[0082] From Table 5, in Examples 13 and 14, the average primary particle diameter d A The metal oxide and component (B) have an average particle diameter D BSince an external preparation containing a specified mass ratio of non-disintegrating particles having a specified range is applied, it has a high adhesion suppression effect and provides a good feel (smooth feel) after application to the skin. [Industrial Applicability]

[0083] The adhesion inhibiting method of the present invention is highly effective in inhibiting the adhesion of atmospheric hazardous substances and is therefore particularly useful as a method for inhibiting the adhesion of atmospheric hazardous substances to the skin. [Explanation of symbols]

[0084] 1: Sample to be evaluated 2:Support 3: Mesh sieve 4: Air hazardous substances for evaluation 5: Blower

Claims

1. A method for suppressing adhesion of atmospheric hazardous substances to the skin by applying an external preparation to the skin, comprising: The topical preparation comprises the following components (A) and (B): Component (A): Average primary particle diameter d A A metal oxide having a thickness of 5 nm or more and 50 nm or less Component (B): Average particle diameter D B Non-disintegrating particles having a size of 1 μm or more and 10 μm or less Contains Component (A) is at least one selected from titanium oxide and zinc oxide, and the surface of which has been subjected to a hydrophobic treatment; the component (B) is at least one selected from composite particles (B1) in which at least a portion of the surface of a core particle (b1-1) is covered with inorganic fine particles (b1-2) and porous particles (B2); The method for inhibiting adhesion of atmospheric hazardous substances, wherein the mass ratio [(A) / (B)] of the content of component (A) to the content of component (B) in the topical preparation is 0.30 or more and 5.0 or less.

2. The amount of component (A) applied to the skin is 0.03 mg / cm 2 The method for inhibiting adhesion of atmospheric hazardous substances according to claim 1 .

3. 3. The method for suppressing adhesion of atmospheric hazardous substances according to claim 1 or 2, wherein the content of component (A) in the topical preparation is 1% by mass or more and 40% by mass or less.

4. The amount of component (A) applied to the skin is 0.8 mg / cm 2 4. The method for inhibiting adhesion of atmospheric hazardous substances according to claim 2 or 3, wherein:

5. 5. The method for suppressing adhesion of air hazardous substances according to claim 1, wherein the core particles (b1-1) constituting the composite particles (B1) are at least one type selected from poly(meth)acrylate particles and silica particles.

6. The method for suppressing adhesion of atmospheric hazardous substances according to any one of claims 1 to 5, wherein the surface of the core particle (b1-1) constituting the composite particle (B1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines.

7. 7. The method for suppressing adhesion of air hazardous substances according to any one of claims 1 to 6, wherein the inorganic fine particles (b1-2) constituting the composite particles (B1) are one or more selected from titanium oxide and zinc oxide that have been surface-treated with one or more selected from silica, hydrous silica, and aluminum hydroxide.

8. The following components (A) and (B): Component (A): Average primary particle diameter d A A metal oxide having a thickness of 5 nm or more and 50 nm or less Component (B): Average particle diameter D B Non-disintegrating particles having a size of 1 μm or more and 10 μm or less Contains Component (A) is at least one selected from titanium oxide and zinc oxide, and the surface of which has been subjected to a hydrophobic treatment; The component (B) is a composite particle (B1) in which at least a part of the surface of a core particle (b1-1) is coated with an inorganic fine particle (b1-2), The core particle (b1-1) is at least one selected from poly(meth)acrylate particles and silica particles, the surface of the core particle (b1-1) is coated with one or more binders (c) selected from the group consisting of poly(N-vinylpyrrolidone), poly(meth)acrylamide, and homopolymers or copolymers of oxazolines; the inorganic fine particles (b1-2) are one or more selected from titanium oxide and zinc oxide that have been surface-treated with one or more selected from silica, hydrous silica, and aluminum hydroxide; A topical preparation, in which the mass ratio of the content of component (A) to the content of component (B) [(A) / (B)] is 0.30 or more and 5.0 or less.

Citation Information

Patent Citations

  • Pollen adsorption-preventing agent

    JP2005336056A

  • Water-in-oil emulsion cosmetic and skin care method

    JP2013107887A

  • Sunscreen cosmetic

    JP2018070556A

  • Anti-dust cosmetic composition with micro bump forming agent

    KR1020180006536A

  • Cosmetic composition for blocking Fine dust with Skin frictional force reducing agent

    KR1020180012909A